A survey on factors influencing investor’s awareness to invest in Prudential Islamic Trust Fund / Muhammad Zulhusni Mohd Amir - Mohd Amir, Muhammad Zulhusni (Faculty of Business and Management, 2011)
This study is conducted to identify the awareness of people toward Prudential Islamic Trust Fund. A set of questionnaire was randomly distributed to 50 respondents in collecting the data. The questionnaire is designed to test the respondent awareness about Prudential Islamic Trust Fund. This questionnaire has distributed to peoples around Malacca City. The independent variables that be used are sales force, fund strength, brand and lastly economic situation. Likert scale is the best type that be used in most questions to determine the level of understanding how strongly agree or strongly disagree of the respondent with the statement regarding the principles. The method used for this study is correlation coefficient analysis. The results then have been interpreted base on correlation coefficient, frequencies and reliability analysis. As the conclusion of this study, this report presents the results of the study related to the issue of Prudential Islamic Trust fund.